THE DEVELOPMENTAL STATE MODEL IN THE ERA OF GLOBALIZATION - Vladislav Dmitriyevich Nayman (Современная наука и инновации, 2022)
The article describes developmental state model that influenced the economic growth of countries in North-East and South-East Asia at the end of the 20th - beginning of the 21st century. The key characteristics of this model are considered and the effectiveness of developmental state model is analyzed. We analyze specifics of capitalism model applied in Asian countries (South Korea, Japan, Singapore, Malaysia), relationship between business and government and role of political system in economic development as well as specific features of different political systems in considered states. This article is based on comparative analysis - we consider similarities and differences between state model applied in North-East Asia and SouthEast Asia. The model of the state of development is also considered from the point of view of critical remarks addressed to it. Moreover, this article analyzes the relevance of this model in the 21st century. Critical remarks mostly refer to outdatedness of development-state model in modern political and economic context. However, we focus on economic structure of South Korea, Japan, Singapore, Malaysia and Indonesia showing big share of high tech production and research and development costs, that shows willingness and ability of these countries to successfully integrate in modern economy in the 21st century, or this model is outdated and is not viable in modern realities. The main purpose of this article is to answer the question whether development-state model is still relevant.